BIMTEK KEPEMIMPINAN DAN TINDAKAN PEMBELAJARAN KEPALA SEKOLAH DALAM SATUAN PEDIDIKAN DI KOTA PALEMBANG TAHUN 2022 - R.A. Zubaidah; Yohanes Susanto; Dheo Rimbano; Gunadi Gunadi; Irwan Pancasila (Nindikayla Institute, 2023)
This community service activity is motivated by the not yet optimal leadership learning for school principals. The purpose of this community service is to optimize the principal learning leadership skills in the era of the industrial revolution 4.0. The solution to this problem is to provide training to principals on action-based learning leadership, namely: analysis of real situations; involve the team; conducting in-depth interviews and reflection; formulate actions and implement actions. The topic of training material is tailored to the needs of school principals, namely the concept of learning leadership, learning activities that are integrated with the curriculum and the development of the teaching profession. This activity received an extraordinary response from the principal of the school. There is an increase in the ability and knowledge of school principals about learning leadership. They really want this activity to be continued in the future so that the principal's learning leadership is more optimal